Properties of Novel Polyesters Made from Renewable 1,4‐Pentanediol - Stadler, Bernhard M.; Brandt, Adrian; Kux, Alexander; Beck, Horst; Vries, Johannes G. (ChemSusChem, 2020)
Novel polyester polyols were prepared in high yields from biobased 1,4‐pentanediol catalyzed by non‐toxic phosphoric acid without using a solvent. These oligomers are terminated with hydroxyl groups and have low residual acid content, making them suitable for use in adhesives by polyurethane formation. The thermal behavior of the polyols was studied by differential scanning calorimetry, and tensile testing was performed on the derived polyurethanes. The results were compared with those of polyurethanes obtained with fossil‐based 1,4‐butanediol polyester polyols. Surprisingly, it was found that a crystalline polyester was obtained when aliphatic long‐chain diacids (>C12) were used as the diacid building block. The low melting point of the C12 diacid‐based material allows the development of biobased shape‐memory polymers with very low switching temperatures (<0 °C), an effect that has not yet been reported for a material based on a simple binary polyester. This might find application as thermosensitive adhesives in the packaging of temperature‐sensitive goods such as pharmaceuticals. Furthermore, these results indicate that, although 1,4‐pentanediol cannot be regarded as a direct substitute for 1,4‐butanediol, its novel structure expands the toolbox of the adhesives, coatings, or sealants formulators. Adhesives are going green! 1,4‐Pentanediol obtained through hydrogenation of γ‐valerolactone can be efficiently converted to 100 % biobased polyester polyols. These oligomers provide added value beyond renewability in adhesive and polyurethane applications.